Introduction to AR-Based Gymnastic Equipment & Movement Variations - Sambegana, Jaka Rahmat; Handayani, Irma (Kirana Publisher (KNPub), 2025)
Silver Gym is a fitness center in the Kasihan area, Bantul, Yogyakarta which provides various types of exercise equipment such as dumbbells, Smith machines, treadmills and others. The problem faced by Silver Gym in Kasihan, Bantul, Yogyakarta, is the wide variety of gymnastic equipment and movements that are difficult for members to memorize and understand, often leading to incorrect execution and muscle injuries. This issue arises due to a lack of knowledge regarding the correct use of equipment and movements. To address this, the research aims to design and develop an augmented reality (AR)-based application that introduces gym equipment and exercise variations, helping users understand the function and proper usage of the equipment. The application is developed using Unity 3D and is equipped with 3D objects and information about the names and functions of the gym equipment. The methodology used in this research involves the design and implementation of AR technology within the application. The result of the study is the creation of an AR-based application that provides interactive visual knowledge to users, with the goal of reducing injury risks due to incorrect movements and maximizing the workout results for Silver Gym members.